2018
DOI: 10.4081/nursrep.2018.6761
|View full text |Cite
|
Sign up to set email alerts
|

The use of videoconferencing in nursing for people in their homes

Abstract: The aim of this literature review is to bring to the forefront knowledge about the suitability of videoconferencing in nursing for patients and their families living at home. A systematic literature review that included studies of videoconferencing in nursing care. Inclusion criteria were original studies relevant to concept of study. Computerized bibliographic databases (PubMed, CINAHL and PsycINFO) were searched from January 2008 to October 2016. In total, 325 articles were identified. Eight articles (1539 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…The main limitations of our study are related to technical problems during simulated video consultations, and these problems were aggravated by the internet connection overload during the COVID-19 confinement, as both tele-working and online classrooms were widespread. However, technical problems usually occur also in real-life video consultations, and their effectiveness is related to adequate network access and the correct functioning of technology [21,22,56]. Lastly, the high student satisfaction with simulated video consultations obtained in our study should be confirmed by other studies, so more research is needed in this field.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The main limitations of our study are related to technical problems during simulated video consultations, and these problems were aggravated by the internet connection overload during the COVID-19 confinement, as both tele-working and online classrooms were widespread. However, technical problems usually occur also in real-life video consultations, and their effectiveness is related to adequate network access and the correct functioning of technology [21,22,56]. Lastly, the high student satisfaction with simulated video consultations obtained in our study should be confirmed by other studies, so more research is needed in this field.…”
Section: Discussionsupporting
confidence: 52%
“…Before this pandemic, video consultations were mainly used with patients who had problems accessing the healthcare services [18], for medical consultations in primary and hospital care [19,20], and for chronic disease conditions [21][22][23]. In addition, video consultations were also used for communication between healthcare professionals and clinicians [24].…”
Section: Introductionmentioning
confidence: 99%
“…The use of information and communication technology (ICT) has a long history [ 10 ]. Although ICT like VC are more commonly used in surgical treatment, there are few studies on the use of VC as a tool in primary cancer care [ 11 13 ]. Accessibility to healthcare can be promoted by VC [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of VC can give patients access to health care personnel without staff or patients having to spend time and effort traveling. Compared to verbal telephone follow-up, VC can also generate richer, more in-depth conversation by allowing the use of body language, and research has shown that patients in community care have found that VC counseling and guidance is similar to faceto-face meetings [7,[16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Despite the increasing number of studies on the implementation, training and use of telehealth using VC as a tool in primary care, few studies have been conducted on the implementation process for home-based cancer care [6,7,20,32]. Therefore, there is a need for knowledge about the implementation and influence of VC in follow-up care.…”
mentioning
confidence: 99%